(Trans)ciberativismo, saberes e vivências de travestis no twitter: um estudo sobre (re)construção discursiva - Freitas, Marcos Randall Oliveira de (2023)
This thesis aims to investigate the discursive (re)construction of the knowledge and experiences of transvestites on Twitter, based on practices of (trans)cyberactivism, considering the textual, discursive and social strategies that implement resistance practices. By discursive reconstruction, we understand the phenomenon that these practices are transformed into counter-discourses. The theoretical basis that supports this objective comes from the interface between Critical Discourse Analysis (FAIRCLOUGH, 2001) and Transvestite Epistemologies (BENEVIDES and LEE, 2018). In this research, we chose to use the three-dimensional conception of discourse, proposed by Fairclough, in 1992, due to our categories of analysis involving the three dimensions – textual, discursive and social – with an emphasis on discursive reconstruction based on the transactivists' counter-discourses. Furthermore, we use Queer Studies (BUTLER, 2008) to confirm that the experiences and knowledge built outside the walls of universities, today, break the barriers of academicism and coloniality, breaking with the invisibilizations imposed by the colonizing model. The methodology used is qualitative, which allows a rapprochement between researcher and research participants, enabling the nuances of what is said and what is not said to provide insurgent data about transvestites. The technique used to generate data is based on virtual ethnography. We chose to practice this technique silently in order to perceive the said and unsaid in order to reduce the researcher's interference in the practices of (trans)cyberactivism. We chose to build the data based on the profiles of 4 (four) transvestites, choosing 5 (five) tweets from each of them. Thus, the research corpus consisted of 20 tweets that were systematized based on the categories analyzed through an undisciplinary, transgressive and emancipatory perspective through the debates and strategies forged by transvestites in the process of resistance and strengthening of identity crossings. An analysis of this data allows us to reach results that show that (trans)cyberactivists use the impositions of the cystema to uncover the contradictions constructed by cisheternormativity, based on textual and discursive constructions permeated by counter-discourses. Thus, a still partial conclusion shows us that the (trans)formed paths and possible interfaces under the bias of queerification of linguistic studies transgress binarism and denaturalize current hegemonic norms, highlighting that trans-radicality strengthens the (de) sewing together the knowledge and experiences of transvestites based on the powers woven into individualities-collectivities constructed beyond hatred, invisibilities and interdictions imposed by cisheteronormativity.